Penerapan Mediasi Penal Dalam Penanganan Kasus Tindak Pidana Di Wilayah Hukum Kepolisian Sektor Bantan Kabupaten Bengkalis - Siti Zuleha; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Penal mediation is one form of dispute resolution outside the judiciary (non litigation) with the helpof other people or third parties who are neutral and do not take sides with either party. There are severallegal bases for the application of penal mediation in Indonesia, namely: National Police Letter of theRepublic of Indonesia No Pol: B / 3022 / XXI / 2009 / SDEOPS, December 14, 2009, Regarding CaseHandling Through Alternative Dispute Resolution (ADR), this letter becomes a reference for the Police tosettle criminal cases through the principle of deliberation and consensus, and respect for social / customarylegal norms and based on justice for the parties, if a case is still in the process of investigation andinvestigation.This research is sociological or empirical research, namely the type of research that uses communityassumptions in looking for facts that occur in the field to answer an existing problem. This research wascarried out in the Riau High Prosecutor's jurisdiction. While the population and sample are parties relatedto the problems examined in this study, the data sources used, primary data, secondary data, and tertiarydata. The technique of collecting data in this study was through interviews and literature review.From the results of the research the authors concluded, the first Settlement of a criminal offense inthe Bantan Sector Police of Bengkalis Regency still uses deliberations between victims and perpetratorsattended by people in the village to reach a decision based on the provisions set by the people In the village,if the reasoning mediation process is carried out, the investigation process in the police of the bus sector isstopped and will not proceed to the Court. Second, the reasons for the police officers to carry out criminalmediation in criminal cases include because in general the perpetrators or the families of the perpetratorsask the investigators that the case is not processed further, the perpetrators / families of the perpetratorsgenerally provide compensation to the victims, so that this is an effort take the victim's heart so as not to suefurther.Keywords: Penal Mediation - Case Handling - Crime.